Painting as policy. Issue 1 (15th June 2005) - Etheredge, J A
Abstract : Ours is, at its heart, a profession of service predicated on mutual trust. All too often policies aimed at resolving a particular problem in health care are inadequate not because they fail at what they were intended to do, but rather because of the unintended consequences, both direct and indirect, that are inevitable in complex systems where competing interests preclude unity of purpose. Ultimately, these policy "layers" distance us from our foundational principles and the disjointed complexity that ensues alienates the patient, disheartens and disillusions the physician, and further undermines the relationship that is so crucial to proper health care delivery. Importantly, we must realise that legislative complexity simply cannot make up for an absence of trust and instead work to foster such trust by reflecting our profession's tradition of service to the public through a blatant, highly visible pursuit of patient welfare.